Pengumuman Stock Buyback dan Reaksi Pasar Saham (Studi Kasus Perusahaan di Bursa Efek Indonesia) - Adhi Suwanto; I Made Sudana (Jurnal Manajemen dan Bisnis Indonesia, 2014)
This study aims to examine the stock market reaction to the announcement of the stock buy back with two indicators of AAR and CAAR. The sample taken is a company that does the announcement of stock buy back in the period 2008 - 2013. Study also tested the market reaction between two groups of companies announcing stock buyback based on BAPEPAM-LK regulations are used. The first group are companies conducting announcements of stock but back by BAPEPAM-​​LK regulations number XI.B.2 which is rules on stock buy back under normal conditions and the second group by BAPEPAM-LK regulation number XI.B.3 which is rules on stock buy back on market conditions potentially crisis. The results showed that there was a significant positive market reaction around the announcement of the stock buy back as indicated by the value of AAR and CAAR are significant. The results also showed that there were significant differences in market reaction between companies that stock buy back announcements reference to BAPEPAM -LK regulations number XI.B.2 with the companies referring to BAPEPAM -LK regulations number XI.B.3. Market reaction to the company that conducting stock buy back announcements with reference to the rules BAPEPAM-LK number XI.B.2 have been reacted all positively, whereas the company that refers to BAPEPAM -LK regulation number XI.B.3 there are some that have been reacted negatively. Keywords : Buy back, Abnormal return, BAPEPAM-LK Regulation